Indirect fluorescent-antibody test for human cytomegalovirus infection in the absence of interfering immunoglobulin G receptors. - Swack, N S (1977)
The presence of immunoglobulin G receptors in human fibroblasts infected with human cytomegalovirus (CMV) resulted in a nonspecific cytoplasmic reaction in the indirect fluorescent-antibody test. Both CMV antibody-positive and antibody-negative sera from human or other animal species produced the cytoplasmic reaction. The substitution of a simian CMV strain for the human virus successfully eliminated this cytoplasmic reaction and, thus, allowed for the observation of virus-induced fluorescent intranuclear inclusions. With the latter system, CMV antibody titers in human sera were equivalent to those obtained by using the human virus and, in addition, allowed for the detection of relatively low-titered serum samples in which antibody measurement was difficult when human CMV-infected cells were used in the indirect fluorescent-antibody test.